فکر اقبال کی عصری معنویت جدید نو آبادیاتی تہذیبی تناظر میں : Contemporary Significane of Iqbal’s Thought in Modren Neodemographic Content - Tahir, Jahangir; Farooq, Dr. Fayyaz Ahmed (Al-Irfan, 2023)
After the 2nd Word War, the United States emerged as a new super power and planned indirect political, economical and cultural rule instead of direct control. For this purpose the European Countries under its rule gathered to form a “Neo-Colonial System” and laid foundation of some institutions like IMF, WTO and World Bank. Today, these institutions have become the arms of imperial powers and the policies of weaker countries are controlled by international aids, provision of loans, investment facilities and technological advancement. The same imperialist spirit of Kippling “White Man’s Burdon” is seen in the ideas of Fokoyamha and Hitington. This neo-imperialism is built on the ideas like cultural hegemony, capitalism and political oppression. Allama Iqbal is a great Muslim figure of the 20th century who is remembered as a representative of anti-colonialism. His poetry and prose is an expression of different aspects of anti-colonialism. In his creations, the intensity of passion along with the intellectual and spiritual depth has been present in the highest degree. This is the sign of the living thinker that the meanings of his thoughts unfold over time. Even today, his universal thought can be a beacon for us against neo-colonialism with its full contemporary meanings.